Unveiling Corporate Transparency: Ownership Dynamics and Earnings Manipulation in Stock Markets - Asad Haider Kanth; Muzafar Hussain Shah; Shehar Yar Khan (Research Journal of Psychology, 2025)
This research examines how corporate transparency and ownership patterns affect earnings manipulation in Pakistani publicly listed companies using a dynamic panel framework. A two-step system GMM estimator is employed, analyzing data from firms listed on the Pakistan Stock Exchange between 2008 and 2018. Findings indicate that robust corporate transparency significantly reduces earnings manipulation. Enhanced disclosure practices lead to decreased managerial discretion in smoothing earnings, suggesting that firms with greater transparency experience lower levels of earnings management. Additionally, ownership structures, such as those dominated by family or institutional investors, exert a significant negative effect on earnings manipulation. These factors establish an effective governance mechanism that curbs managerial control over earnings. Consequently, the study highlights that strong corporate disclosure combined with family or institutional ownership plays a pivotal role in minimizing earnings management practices within the Pakistani market.